Explosive growth in African combustion emissions from 2005 to 2030 - (:unkn) unknown (My University, 2014)
Emissions of gases and particles from the combustion of fossil fuels and biofuels in Africa are expected to increase significantly in the near future due to the rapid growth of African cities and megacities. There is currently no regional emissions inventory that provides estimates of anthropogenic combustion for the African continent. This work provides a quantification of the evolution of African combustion emissions from 2005 to 2030, using a bottom-up method. This inventory predicts very large increases in black carbon, organic carbon, CO, NOx, SO2 and non-methane hydrocarbon emissions if no emission regulations are implemented. This paper discusses the effectiveness of scenarios involving certain fuels, specific to Africa in each activity sector and each region (western, eastern, northern and southern Africa), to reduce the emissions. The estimated trends in African emissions are consistent with emissions provided by global inventories, but they display a larger range of values.African combustion emissions contributed significantly to global emissions in 2005. This contribution will increase more significantly by 2030: organic carbon emissions will for example make up 50% of the global emissions in 2030. Furthermore, we show that the magnitude of African anthropogenic emissions could be similar to African biomass burning emissions around 2030.
Keywords: African Research